Effectiveness of The Public Service Mini Mall (MMPP) Sukodono District Sidoarjo Regency - Riska Ayu Rahmaida; Muhammad Agus Muljanto (Publik : (Jurnal Ilmu Administrasi), 2026)
The state is responsible for fulfilling the basic rights and needs of every citizen through the provision of accessible, efficient, and high-quality public services. One strategic initiative to achieve this objective is the establishment of Public Service Malls (MPP), which integrate multiple public services in a single location. To expand service accessibility, the Sidoarjo Regency Government introduced the Mini Public Service Mall (MMPP) in Sukodono District, the first district-level MPP innovation in Indonesia. However, several implementation challenges have raised concerns regarding its effectiveness in delivering integrated public services. This study aims to analyze and describe the effectiveness of public service delivery at the Mini Public Service Mall (MMPP) in Sukodono District, Sidoarjo Regency. A descriptive qualitative approach was employed using three dimensions of effectiveness: goal achievement, integration, and adaptation. Data were collected through observations, semi-structured interviews, and documentation using purposive sampling and analyzed through an interactive qualitative analysis process. The findings reveal that the overall implementation of public services at the MMPP remains ineffective. Of the eleven service counters initially established, only five continue to operate, while limited human resources, inconsistent service availability, unpublished standard operating procedures, and inadequate inter-agency coordination have reduced service effectiveness. Although several counters have demonstrated satisfactory performance in meeting community needs, the MMPP has not yet fully achieved its intended objectives of providing integrated, accessible, and responsive public services. Strengthening institutional collaboration, workforce allocation, and service management is therefore essential to improve the sustainability and effectiveness of the MMPP model.